2009
DOI: 10.1210/jc.2008-2615
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Thyroid Function Tests over 5 Years in a Large Pediatric Cohort

Abstract: In the pediatric population, initial normal or slightly elevated TSH levels are likely to remain normal or spontaneously normalize without treatment. Patients with initial levels greater than 7.5 mIU/liter, particularly girls, are at a greater risk for sustained abnormal TSH levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
4
12

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(125 citation statements)
references
References 25 publications
7
102
4
12
Order By: Relevance
“…However some studies found no relationship between weight loss and normalization of TSH values [26,27]. Our current knowledge does not support the use of thyroxine treatment for elevated TSH in obese children [28,29].…”
Section: Discussioncontrasting
confidence: 70%
“…However some studies found no relationship between weight loss and normalization of TSH values [26,27]. Our current knowledge does not support the use of thyroxine treatment for elevated TSH in obese children [28,29].…”
Section: Discussioncontrasting
confidence: 70%
“…In pediatric age, SH is detected with increasing frequency, as thyroid function tests are routinely performed in children with very different clinical problems (2,3). SH may be possibly caused by the same thyroid disorders that result in overt thyroid function impairment, in particular, Hashimoto's thyroiditis (HT) (4).…”
Section: Introductionmentioning
confidence: 99%
“…Genel olarak yayınlarda ise çocuklarda %2 erişkinlerde ise %1-10 arasın-da tespit edilmiştir [4,13,16]. Hindistan'da Marwaha'nın 39961 çocuk ile yaptığı çalışmada %6,1 SH tespit edilmiş-tir [12].…”
Section: Epidemiyolojiunclassified
“…Lazar ve ark. retrospektif analizlerinde 6 ay ve 6 yaş arasında TSH değeri 5,5-10 mIU/L olan çocukların oranı %2,9 olarak bulunmuştur [16].…”
Section: Epidemiyolojiunclassified
See 1 more Smart Citation